Pengaruh Persepsi Mahasiswa Tentang Koperasi Terhadap Minat Berkoperasi Mahasiswa Pendidikan Ekonomi - Artin, Endah Aisah Eka Yuni; Kamalia, Putri Ulfa (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This research aims to determine the influence of student perceptions about cooperatives on economic education students' interest in cooperatives. This research is a causal quantitative research, with 79 students as respondents. Data collection technique by distributing Google form links online. The research instrument used in this research was a questionnaire. The data analysis method used is simple linear regression. The results of this research show that students' perceptions of cooperatives have a positive influence on students' interest in cooperatives. Things that can be done to increase economic education students' interest in cooperatives include providing project-based assignments, student internship programs in cooperatives, creating a family atmosphere in cooperatives, creating innovation in the products offered and the need to improve cooperative management. So with these steps, economic education students' interest in cooperatives will increase.